Ecosystem Model of Tourism Village in Urban Area: Case Study of Denpasar City, Bali - Arismayanti, Ni Ketut; Pitana, I Gde (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
Tourism villages in urban areas are a one-of-a-kind and rare product in the midst of the city's hustle and bustle and high mobility. Denpasar City has six tourism villages: Serangan, Sanur Kauh, Kertalangu, Sanur Kaja, Penatih, and Sanur; however, the development of tourism villages has fallen far short of expectations and failed to serve as a model for other tourism villages. The primary barrier to inclusive and sustainable development is a lack of stakeholder participation and collaboration. Creating a sustainable tourism village ecosystem model is critical for managing resources, empowering communities, and increasing regional appeal and income through collaboration and innovation. The purpose of this study is to create a tourism village ecosystem model and clarify the roles of the actors involved. Based on the existing model, obstacles to tourism village development can be identified, with the goal of designing an ideal model that can be used as a reference for other tourism villages. The tourism village ecosystem model in Denpasar City emphasizes collaboration among various actors to create mutually beneficial synergies, focusing on improving tourist experience quality, preserving culture and the environment, and improving local community welfare. Tourism villages in urban areas provide uniqueness by integrating local cultural elements and city dynamics, allowing them to serve as alternative tourist destinations. These tourism villages have the potential to serve as role models for the development of tourism in other urban areas by focusing on sustainability and community empowerment.